Land Surface Temperature Estimation After A Decade of Aceh Tsunami (Case Study of West Aceh District of 2013 Data). Issue 1 (September 2020) - Rusdi, M; Suri, N A; Nizamuddin; Ardiansyah; Sugianto; Muzailin; Jefriza
Abstract: Thermal images of Landsat satellite can be utilized by estimating the land surface temperature. Moreover, retrieving the temperature estimation before the current event can be done using temporal analysis. Land surface temperature estimation requires Land Surface Emissivity (LSE) value through the Normalized Difference Vegetation Index (NDVI) approach. The result showed that the average land surface temperature in West Aceh District in 2013 was 26.07 °C. The result also showed that the spatial distribution of temperature spread accordingly following the transect pattern. The temperature in the coastal areas was higher than the hinterland. This phenomenon is due to high built-up in the coastal regions, whereby vegetation is dominant in the hinterland areas.